Potency of agricultural wastes in mushroom (Pleurotus sajor-caju) biotechnology for feeding broiler chicks (Arbor acre) - Charles Oluwaseun Adetunji; Isaac Oluseun Adejumo (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Nigeria produces large quantities of wastes per year, which are underutilised and constitute environmental nuisance. The effect of dietary mycomeat produced from ogi production wastes based on yellow maize using wild and mutant strains of Pleurotus sajor-caju was assessed based on chickens’ growth, haematology and histology. Methods The wastes were air-dried for 72 h. The inoculum was developed by transferring loopful of inoculum into the prepared inoculum medium. Incubation was carried out at 37 ± 1 °C. 144 1-day-old chicks were used. The trial lasted for 21 days. The chicks were grouped into 4, each containing 36 1-day-old chicks. The animals were provided with fresh feed and water ad libitum. Feed intake and body weight were measured weekly, while the calculation of feed conversion ratio (FCR) and weight gain was based on the data obtained. Results Feed intake was lower for birds fed diets containing ogi production wastes and mycomeat produced from ogi production wastes using a mutant strain of P. sajor-caju. No significant differences were observed for body weight gain amongst the treatments. Mycomeat produced from ogi production wastes using a mutant strain of P. sajor-caju and ogi production wastes enhanced FCR, while those on wild strain of P. sajor-caju did not differ significantly from other treatments. Conclusion Inclusion of mycomeat in the diet of broiler chicks is considered safe and could promote growth.